2011
DOI: 10.18632/aging.100394
|View full text |Cite
|
Sign up to set email alerts
|

Ishemia-Reperfusion enhances GAPDH nitration in aging skeletal muscle

Abstract: Aging and skeletal muscle ischemia/reperfusion (I/R) injury leads to decreased contractile force generation that increases severely with age. Our studies show that glyceraldehyde-3-phosphate dehydrogenase (GAPDH) protein expression is significantly decreased at 3 and 5 days reperfusion in the young mouse muscle and at 1, 3, 5, and 7 days in the aged muscle. Using PCR, we have shown that GAPDH mRNA levels in young and old muscle increase at 5 days reperfusion compared to control, suggesting that the protein def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…They focused on the anti-MDR and anti-inflammatory activities of the compounds. 105 It was concluded that in case of euphodendroidins a free OH group at C-3, together with the negative effect of this group at C-2 were needed for the anti-MDR activity.…”
Section: Characias E Peplus E Paralias and E Helioscopia)mentioning
confidence: 99%
See 1 more Smart Citation
“…They focused on the anti-MDR and anti-inflammatory activities of the compounds. 105 It was concluded that in case of euphodendroidins a free OH group at C-3, together with the negative effect of this group at C-2 were needed for the anti-MDR activity.…”
Section: Characias E Peplus E Paralias and E Helioscopia)mentioning
confidence: 99%
“…Finally, in case of pepluane series investigated, pepluanin A with acetyl group at C-8 and nicotinoyl group at C-9 was found to be the most potent inhibitor of Pgp. 105 …”
Section: Characias E Peplus E Paralias and E Helioscopia)mentioning
confidence: 99%
“…Few studies previously examined the effect of hindlimb IR in aged rodents [34,35]. Aged skeletal muscles exhibited more damage and/or defective regeneration following IR [34] and experienced greater oxidative stress, protein modification, and GAPDH degradation, likely contributing to decreased muscle function [35]. Accordingly, the mitochondrial ischemic insult appeared more severe in senescent rats with a more profound decrease in V Max after IR (À70%) as compared to the decreases we previously reported using the same experimental setting in young animals (À36%) [25].…”
Section: Ischemia-reperfusion Induced Significant Impairments In Agedmentioning
confidence: 99%
“…Recently, considerable attention has been devoted to known compounds jatrophane and lathyrane type which are non-phorboid structures, but have been considered to be potent modulators of MDR. [10][11][12][13][14][15][16][17][18] However, a few types of lathyrane diterpenes were found and only the different substitutions related to anti-MDR bioactivity were focused. 15 The structure-activity relationship has not been elaborated from the aspect of different skeletons.…”
Section: Introductionmentioning
confidence: 99%